Effect of innovation orientation of high-tech SMEs “small and mid-sized enterprises in China” on innovation performance - Tong, Tong; Abd Rahman, Azmawani (MDPI, 2022)
Mass entrepreneurship and innovation refer to encouraging the broad masses of the people, including industry, agriculture, commerce, education, and soldiers, to participate in entrepreneurship, encouraging all Chinese people to participate in innovation, which Premier Li put forward at the 2014 Summer Davos Forum in Tianjin. After seven years of development, the innovation orientation of mass entrepreneurship and innovation has become an important engine leading China’s economic growth in the future. This research aims to examine the effect of innovation orientation on enterprise innovation performance. Based on a survey of 378 high-tech SMEs in Sichuan Province, China, structural equation modeling (SEM) was employed to examine the research model. The result shows that innovation orientation and organizational flexibility significantly affect enterprise innovation performance. Among the effects of innovation orientation on enterprise innovation performance, capability and resource flexibility play mediators. This research disclosed that important factors affecting the innovation performance of high-tech SMEs enterprises include resource flexibility and capability flexibility. To give better play to the positive impact of innovation orientation, we should strengthen the flexible strategy of organizations. Thus, committed to more flexible market development, promoting the vigorous development of new technologies, new industries, and new formats, and realizing the growth of enterprise innovation performance.